2020
DOI: 10.21203/rs.3.rs-40418/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilizing ultrasound findings of a single indicator joint to assess non-systemic juvenile idiopathic arthritis

Abstract: Background: Musculoskeletal ultrasound (MSUS) has been used worldwide in adult patients with rheumatoid arthritis (RA) but is beginning to play an increasing role in patients with juvenile idiopathic arthritis (JIA). The aim of this study was to investigate the application of MSUS findings of a single indicator joint in JIA to assess the disease activity and classify disease subtype.Methods: Thirty-five non-systemic JIA patients with a total of 62 visits were retrospectively recruited in this study. Among the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Our study showed no signi cant difference in disease severity between JIA subtypes. In agreement with our results, Huang et al 2021 (37) studied thirty-ve non-systemic JIA patients with a total of 62 visits. JIA disease activity was shown as the physician's global assessment of disease activity (PGA) score.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed no signi cant difference in disease severity between JIA subtypes. In agreement with our results, Huang et al 2021 (37) studied thirty-ve non-systemic JIA patients with a total of 62 visits. JIA disease activity was shown as the physician's global assessment of disease activity (PGA) score.…”
Section: Discussionsupporting
confidence: 92%